Fiscal Policy and Business Cycles in an Oil-Producing Economy : The Case of Venezuela - Baldini, Alfredo (IMF Working Papers; Working Paper ;, 2005)
This paper analyzes the fiscal policy in Venezuela during 1991-2003, by using a number of statistical approaches to analyze trends and cycles of economic output and fiscal outcomes. The business cycle features a strong dominance of short-term cyclical components-each cycle having an average duration of about two to three years. However, the cyclical volatility of non-oil sector GDP is more than two times as large as the volatility of oil sector GDP. On the fiscal side, while oil revenues are independent of the business cycle, all the other main fiscal variables exhibit strong procyclicality. In particular, fiscal procyclicality is higher during good times than bad times, which could be related to the existence of "voracity effects." The discretionary component of fiscal policy is as volatile as the component induced by the business cycle.